Representation and Resistance South Asian and African Women's Texts at Home and in the Diaspora - Kaur Singh, Jaspal (University of Calgary Press, 2008)
Representation and Resistance: South Asian and African Women's Texts at Home and in the Diaspora compares colonial and national constructions of gender identity in Western-educated African and South Asian women's texts. Jaspal Kaur Singh argues that, while some writers conceptualize women's equality in terms of educational and professional opportunity, sexual liberation, and individualism, others recognize the limitations of a paradigm of liberation that focuses only on individual freedom. Certain diasporic artists and writers assert that transformation of gender identity construction occurs, but only in transnational cultural spaces of the first world-spaces which have emerged in an era of rampant globalization and market liberalism. In particular, Singh advocates the inclusion of texts from women of different classes, religions, and castes, both in the Global North and in the South.